Elimination of Elaidic Acid and Enrichment of Omega-3 Fatty Acid in Industrial By-Product of Fish Processing - Maulana, Indra Topik; Sukrasno, Sukrasno; Damayanti, Sophi (Molekul, 2025)
ABSTRACT. "Minyak Ala Muncar," abbreviated as MAM, is a by-product waste of a fish canning factory in Muncar Banyuwangi, Indonesia. According to GCMS, MAM contains essential fatty acids and trans Fatty Acids such as Elaidic Acid (EA), which could threaten the Indonesian population's health. Several purification methods have been applied to recycle the MAM. But, these methods did not concern the removal of EA from MAM. Even in other studies, the MAM was used as food fortification. Therefore, this study aimed to separate EA from the MAM and produced fractions of oil rich in n-3 fatty acids and free of EA. Three low-temperature crystallization methods, called winterization, namely crystallization with n-hexane, acetone, and urea, were conducted to remove the EA from MAM. The results showed that both crystallization with n-hexane and acetone produced ratio values of PUFA/trans-FA, n-3/trans-FA, EPA/EA, and DHA/EA below 0.3, respectively. While urea crystallization was able to produce ratio numbers for each PUFA/trans-FA, n-3/trans-FA, EPA/EA, and DHA/EA were 1.46 + 0,05;1.36 + 0.04; 0.73 + 0.02; and 0.48 + 0.04. Keywords: Eicosapentaenoic acid, Elaidic acid, Low-temperature crystallization, Urea crystallization, Winterization